IDENTIFIKASI LITOLOGI RESERVOIR BATUPASIR MENGGUNAKAN INVERSI IMPEDANSI ELASTIK DI LAPANGAN “D” PADA FORMASI TALANG AKAR DENGAN KEDALAMAN 2780 – 2805 METER, CEKUNGAN JAWA BARAT UTARA - Dita Aprilina; Agus Setyawan; Mualimin Mualimin (Youngster Physics Journal, 2014)
Elastic Impedance (EI) inversion has been used to determine sandstone lithology distributions in “D” Field of Talang Akar Formation, North West Java Basin. The target zone was TAF-3-1 with depth 2780 m - 2805 m which located in Talang Akar Formation with litologies of sandstone and shale.            Sensitivity analysis is method to separation of sandstone and shale lithology between Elastic Impedance log and Gamma Ray log crossplot at the angle 0º-30º. Analysis at seismic data is inversion result analysis on vertical and to knowning the value of Elastic Impedance and inversion result analysis on horizontal to knowing the direction of sandstone reservoir lithology.            Result of Elastic Impedance inversion shows that sandstone reservoir lithology in target area TAF-3-1 layer have value of Elastic Impedance from 1314 g.m/cm3s - 1410 g.m/cm3s, which can be seen in the vertical cross section of Elastic Impedance. Lithology distribution in lateral showed that reservoir of sandstone in Northwest–Southeast of study area around of well TA-01.Keywords : Elastic impedance inversion, elastic impedance, sandstone, Talang Akar Formation